The Effect of Habits of Mind on Ability to Construct a Cognitive Instruments with Computerized Systems - Nafiah, Maratun; Riyadi; Noornia, Anton (International Journal of Psychosocial Rehabilitation, 2020)
Future teacher candidates (21st century) possess characteristics including creativity, divergent thinking, critical thinking, mathematical and science competence, digital competence, a sense of initiative, and entrepreneurship. The purpose of this study is to analyze the influence of habits of mind on the ability to construct cognitive instruments of the Mathematics subject in Class V Elementary School with a computerized system. The research method used was surveys on primary school teacher education in Jakarta. In this study, to assess the participants’ habits of mind, questionnaires were used, while to know the ability to construct cognitive, the researcher used a performance test. Furthermore, in analyzing data, the method used was structural equation modeling. As a result, this study found that there were effects of habits of mind on the ability to construct computerized cognitive instruments. Overall, it can be concluded that higher habits of mind can improve the ability to construct cognitive instruments with a computerized system, especially in grade V math subjects in elementary school.